Peran Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar Negeri Salukaili, Kecamatan Baras - Iin Indrawiyani; Hasna Hasna; Suandi Silalahi (CV. ULIL ALBAB CORP, 2025)
This research aims to explore the leadership role of school principals in improving the quality of education at Salukaili State Elementary School (SDN), Baras District. The method used in this research is a descriptive qualitative approach. This approach was chosen because it allows researchers to explore information about the strategies implemented by the principal at SDN Salukaili in improving the quality of education. Through interviews with school principals, teachers and parents, as well as direct observations of school activities, this research succeeded in identifying several strategic steps taken by school principals. Some of the strategies identified in this research include teacher empowerment, results-based management, and change management. Teacher empowerment, as one of the main strategies, includes teacher professional development through training and workshops to improve their competence. Results-based management refers to the school principal's efforts to set clear performance indicators and ensure that every policy and decision taken is oriented towards improving student learning outcomes. Meanwhile, the management of change carried out by the school principal aims to create an environment that supports innovation in the learning process, as well as ensuring positive changes in the education system at the school